A homogenization method for negative electrode slurry
A multi-step stirring process addressing the homogenization challenges of negative electrode slurry by adjusting material ratios and parameters improves production efficiency and battery performance.
Patent Information
- Application Number
- CN202211035531.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-08-26
AI Technical Summary
The homogenization of negative electrode slurry in lithium-ion batteries is challenging due to the looseness and porosity of the negative electrode material, leading to sedimentation and agglomeration, which affects the uniformity and performance of the battery.
A multi-step stirring process is employed, adjusting the mass ratios and stirring parameters based on the particle size, tap density, and specific surface area of the negative electrode material, using dispersants and binders to achieve uniform dispersion and stability.
The method significantly reduces production time and costs while improving the uniformity and consistency of the electrode sheet, enhancing battery performance.
Smart Images

Figure CN115275090B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a method for homogenizing negative electrode slurry. Background Art
[0002] Lithium-ion batteries have high energy density, high operating voltage, environmental friendliness, and strong manufacturing and processing performance. They are currently widely used in mobile phones, laptops, electric vehicles, and energy storage. With the acceleration of people's pace of life and the popularization of intelligent communication devices such as mobile phones, the demand for high energy density batteries is increasing. Sodium carboxymethyl cellulose (CMC) is usually added during the preparation of negative electrode slurry, which can thicken and stabilize the slurry to prevent the sedimentation of negative electrode active substances.
[0003] The negative electrode material has the characteristics of looseness and porosity, with a high specific surface area and low tap density. It is difficult to disperse during the homogenization process, which will cause the slurry to settle and agglomerate. The negative electrode sheets coated with it have poor uniformity, which ultimately affects the battery performance.
[0004] Currently, mainstream companies use methods such as adding dispersants or increasing CMC content to adjust the slurry homogenization problem.
[0005] CN113045777A discloses a negative electrode dispersant and a lithium ion battery containing the same. The negative electrode dispersant is added to improve the stability and uniformity of the negative electrode slurry. However, the dispersant cannot be discharged during the baking process, which has a great impact on the long-term life of the battery.
[0006] CN109802097A discloses a high-capacity cylindrical 18650 lithium-ion battery negative electrode homogenization stirring process, in which sodium carboxymethyl cellulose and deionized water are prepared into a glue solution, and the glue solution is added to the slurry in four times. The slurry stirring time is long, which reduces production efficiency. Summary of the invention
[0007] The object of the present invention is to provide a method for homogenizing negative electrode slurry. The homogenizing method of the present invention can improve production efficiency, reduce manufacturing costs, and improve the uniformity of negative electrode slurry to obtain a highly stable electrode sheet.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for homogenizing a negative electrode slurry, the homogenizing method comprising the following steps:
[0010] (1) mixing a negative electrode material, a conductive agent and a dispersant and stirring them in one step to obtain a mixed material;
[0011] (2) mixing the mixture obtained in step (1) with the first solvent and stirring in two steps to obtain a mixed slurry;
[0012] (3) mixing the mixed slurry obtained in step (2) with the second solvent and stirring in three steps to obtain a half-step slurry;
[0013] (4) mixing the half-step slurry obtained in step (3) with a binder, and stirring the mixture in four steps to obtain the negative electrode slurry;
[0014] Among them, the mass ratio of the negative electrode material, conductive agent and dispersant in step (1) is (90-97):(0.5-0.75)a:a, a=0.17x+0.3y-0.47z, wherein x is the median particle size D50 of the negative electrode material, y is the tap density of the negative electrode material, and z is the specific surface area of the negative electrode material.
[0015] In the homogenization process of the negative electrode slurry described in the present invention, the amount of dispersant added is correlated with the D50, tap density and specific surface area of the negative electrode material. Controlling the relationship between the dispersant and the negative electrode material can reduce the processing difficulty, improve the slurry stability, thereby improving the uniformity and consistency of the electrode sheet and improving the performance of the battery cell.
[0016] The larger the particle size of the negative electrode material, the smaller the specific surface area, so the less dispersant is needed to coat the surface of the negative electrode material. If too much dispersant is added, the viscosity of the slurry will increase, which is not conducive to coating processing. On the contrary, the dispersant will not completely coat the surface of the negative electrode material, and the slurry viscosity will be low, which is also not conducive to coating processing. At the same time, due to the discharge of a large amount of water during baking, it is easy to cause the electrode to crack. The larger the tap density, the greater the slurry packing density, the closer the contact between particles, the more uniform the dispersant coating, and the better the slurry stability. On the contrary, the tap density is low, the negative electrode material packing density is small, the particles are fluffy, and it is extremely difficult to coat the dispersant evenly. Therefore, the slurry stability is poor, and the coating and other processing performance are poor. The larger the specific surface area, the more pores in the negative electrode material, and the more difficult it is for the dispersant to coat evenly. Therefore, the kneading time, dispersant dosage, and shear speed must be increased to varying degrees. The particle size, tap density and specific surface area of the negative electrode material are interrelated. The negative electrode material has a small particle size, a large specific surface area, and a low tap density, so it is difficult to process; while the negative electrode material has a large particle size, a small specific surface area, and a high tap density, so the processing difficulty is relatively easy.
[0017] Preferably, the negative electrode material in step (1) includes any one of graphite, soft carbon, or hard carbon, or a combination of at least two of them.
[0018] Preferably, the conductive agent includes any one of conductive carbon black, graphene or carbon nanotubes, or a combination of at least two of them.
[0019] Preferably, the dispersant comprises sodium carboxymethylcellulose.
[0020] Preferably, the median particle size D50 of the negative electrode material in step (1) is 5 to 20 μm, for example, 5 μm, 10 μm, 12 μm, 15 μm or 20 μm.
[0021] Preferably, the tap density of the negative electrode material is 0.7 to 1.2 g / cm 3 , for example: 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1g / cm 3 , 1.1g / cm 3 or 1.2g / cm 3 wait.
[0022] Preferably, the specific surface area of the negative electrode material is 0.8 to 2.8 m 2 / g, for example: 0.8m 2 / g, 1m 2 / g, 1.5m 2 / g, 2m 2 / g or 2.8m 2 / g, etc.
[0023] Preferably, the stirring speed of the one-step stirring in step (1) is 1000-1800 rpm, for example: 1000 rpm, 1200 rpm, 1400 rpm, 1600 rpm or 1800 rpm, etc.
[0024] Preferably, the stirring time of the step is 20 to 30 min, for example, 20 min, 22 min, 25 min, 28 min or 30 min.
[0025] The one-step stirring in step (1) of the present invention is solid-phase mixing and stirring. Since the conductive agent particles are small and easy to agglomerate, if the stirring speed is too slow, the conductive agent agglomerates will be unevenly dispersed, and if the stirring speed is too fast, the graphite particles will collide with each other and destroy the particle morphology.
[0026] Preferably, in step (2), the first solvent comprises water.
[0027] Preferably, the mass ratio of the mixture to the first solvent is 100:(30-40), for example: 100:30, 100:32, 100:35, 100:38 or 100:40, etc.
[0028] Preferably, the speed of the second-step stirring in step (2) is 500-1200 rpm, for example: 500 rpm, 600 rpm, 800 rpm, 1000 rpm or 1200 rpm, etc.
[0029] Preferably, the linear velocity of the two-step stirring is (0.67-1.23) bm / s, wherein b=7.35a+0.73y.
[0030] Preferably, the second-step stirring time is 30 to 40 min, for example, 30 min, 32 min, 35 min, 38 min or 40 min.
[0031] The two-step stirring process described in step (2) of the present invention is a kneading process, in which the solvent is added to fully wet the negative electrode material, the conductive agent and the dispersant, and the dispersant is dissolved in the solvent. The dispersant macromolecular chain structure is uniformly coated on the graphite particles and the conductive agent by kneading, which plays a thickening role. When the stirring paddle rotates, the slurry with high solid content can be sheared, and the slurry is squeezed at the same time, so that the negative electrode material, the conductive agent and the dispersant chain are mixed more evenly. The stirring linear velocity is associated with the properties of the negative electrode material. Since the solid content of the slurry is high in this step, if the shear linear velocity of the stirring paddle is too fast, the slurry temperature will increase. If the temperature is too high, the long chain structure of the dispersant will be broken and destroyed, and the thickening effect will be lost. At the same time, the coating on the graphite surface is uneven, resulting in unstable slurry viscosity and easy sedimentation. If the shear linear velocity of the stirring paddle is too slow, the slurry is not kneaded completely, and the dispersant coating is not complete.
[0032] Preferably, in step (3), the second solvent comprises water.
[0033] Preferably, the mass ratio of the mixed slurry to the second solvent is 100:(17-28), for example: 100:17, 100:18, 100:20, 100:25 or 100:28, etc.
[0034] Preferably, the speed of the three-step stirring in step (3) is 2000-2700 rpm, for example: 2000 rpm, 2200 rpm, 2400 rpm, 2500 rpm or 2700 rpm.
[0035] Preferably, the linear velocity of the three-step stirring is (0.89-1.56) bm / s.
[0036] Preferably, the three-step stirring time is 20 to 30 min, for example, 20 min, 22 min, 25 min, 28 min or 30 min.
[0037] The three-step stirring of step (3) of the present invention mainly regulates the solid content of the slurry, so that the dispersant is evenly coated on the surface of the negative electrode material at a higher solid content, while ensuring the viscosity and temperature of the slurry to meet the coating conditions.
[0038] Preferably, the solid content of the half-step slurry is 55-62%, for example: 55%, 56%, 58%, 60% or 62%, etc.
[0039] Preferably, the adhesive in step (4) comprises styrene-butadiene rubber.
[0040] Preferably, the mass ratio of the half-step slurry to the binder is 100:(1-3.5), for example: 100:1, 100:1.5, 100:2, 100:3 or 100:3.5, etc.
[0041] Preferably, the stirring speed of the four steps in step (4) is 500-1200 rpm, for example: 500 rpm, 600 rpm, 800 rpm, 1000 rpm or 1200 rpm, etc.
[0042] Preferably, the linear velocity of the four-step stirring is (a×z+3.2y) m / s.
[0043] Preferably, the stirring time of the four steps is 30 to 40 min, for example, 30 min, 32 min, 35 min, 38 min or 40 min.
[0044] The four-step stirring and adding of the binder in step (4) of the present invention mainly plays a bonding role, so that the coated slurry is firmly bonded to the current collector. If the stirring speed in this step is too fast, the binder will demulsify and lose its bonding effect. If the stirring speed is too slow, the binder will be unevenly dispersed, and phenomena such as "floating, blue floating" will occur, and the bonding effect will also fail.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The stirring method of the present invention requires a total of 100-140 minutes from feeding to completion of stirring, which greatly saves the negative electrode homogenization time, improves production efficiency, and reduces production costs.
[0047] (2) The present invention relates the amount of dispersant added to graphite D50, tap density, and specific surface area, and is suitable for stirring and homogenizing all negative electrode materials, with greater universality. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is a 24-hour viscosity change diagram of the negative electrode slurry prepared by the homogenization method described in Example 1. DETAILED DESCRIPTION
[0049] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0050] Example 1
[0051] This embodiment provides a method for homogenizing a negative electrode slurry, the method comprising the following steps:
[0052] (1) Artificial graphite, conductive agent and sodium carboxymethyl cellulose (CMC) were added into a double planetary mixer in a mass ratio of 96.5:1.5:2.0, with a stirring speed of 1500 rpm and a mixing time of 25 min to obtain a mixture, wherein the median particle size of the artificial graphite was D50 = 15 μm and the tap density was 0.95 g / cm 3 , with a specific surface area of 1.8m 2 / g, a=2;
[0053] (2) adding deionized water with a mass fraction of 32% of the mixture, controlling the stirring paddle speed to 1000 rpm, the dispersion line speed to 14.6 m / s, the stirring time to 35 min, and the temperature to ≤28° C. to obtain a mixed slurry, wherein b=15.4;
[0054] (3) adding 22% deionized water to the mixed slurry, controlling the stirring paddle speed to 2300 rpm, the dispersion line speed to 21.1 m / s, the slurry solid content to 57%, and the stirring time to 30 min to obtain a half-step slurry;
[0055] (4) Add 1.5% by mass of styrene-butadiene rubber (SBR) of the half-step slurry, control the stirring paddle speed to 800 rpm / min, control the dispersion line speed to 6.6 m / s, and stir for 30 minutes to obtain the negative electrode slurry.
[0056] The 24h viscosity change of the negative electrode slurry is shown in the figure Figure 1 shown.
[0057] Example 2
[0058] This embodiment provides a method for homogenizing a negative electrode slurry, the method comprising the following steps:
[0059] (1) Artificial graphite, conductive agent and sodium carboxymethyl cellulose (CMC) were added into a double planetary mixer in a mass ratio of 96.2:1.42:2.38, with a stirring speed of 1500 rpm and a mixing time of 25 min to obtain a mixture, wherein the median particle size D50 of the artificial graphite was 15 μm and the tap density was 1 g / cm 3 , with a specific surface area of 1m 2 / g, a=2.38;
[0060] (2) adding deionized water with a mass fraction of 32% of the mixture, controlling the stirring paddle speed to 1000 rpm, the dispersion line speed to 18.2 m / s, the stirring time to 35 min, and the temperature to ≤28° C. to obtain a mixed slurry, wherein b=18.2;
[0061] (3) adding 22% deionized water to the mixed slurry, controlling the stirring paddle speed to 2400 rpm, the dispersion line speed to 21.84 m / s, the slurry solid content to 57%, and stirring time to 30 min to obtain a half-step slurry;
[0062] (4) Add 1.6% by mass of styrene-butadiene rubber (SBR) of the half-step slurry, control the stirring paddle speed to 800 rpm / min, control the dispersion line speed to 5.6 m / s, and stir for 30 minutes to obtain the negative electrode slurry.
[0063] Example 3
[0064] The only difference between this embodiment and embodiment 1 is that the dispersion linear velocity of the second-step stirring in step (2) is 20 m / s, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0065] Example 4
[0066] The only difference between this embodiment and embodiment 1 is that the dispersion linear velocity of the second-step stirring in step (2) is 12 m / s, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0067] Example 5
[0068] The only difference between this embodiment and embodiment 1 is that the mass of SBR is 4% of the mass of the half-step slurry, and the other conditions and parameters are exactly the same as those in embodiment 1.
[0069] Example 6
[0070] The only difference between this embodiment and embodiment 1 is that the mass of SBR is 0.6% of the mass of the half-step slurry, and other conditions and parameters are exactly the same as those in embodiment 1.
[0071] Comparative Example 1
[0072] The only difference between this comparative example and Example 1 is that sodium carboxymethyl cellulose is not added, and other conditions and parameters are exactly the same as those in Example 1.
[0073] Comparative Example 2
[0074] The only difference between this comparative example and Example 1 is that no styrene-butadiene rubber is added, and other conditions and parameters are exactly the same as those in Example 1.
[0075] Comparative Example 3
[0076] The only difference between this comparative example and Example 1 is that various materials are directly mixed with the solvent.
[0077] Comparative Example 4
[0078] The only difference between this comparative example and Example 1 is that the mass ratio of artificial graphite to sodium carboxymethyl cellulose is 96:3, and the other conditions and parameters are exactly the same as those in Example 1.
[0079] Comparative Example 5
[0080] The only difference between this comparative example and Example 1 is that the mass ratio of artificial graphite to sodium carboxymethyl cellulose is 97:1.5, and the other conditions and parameters are exactly the same as those in Example 1.
[0081] Performance Testing:
[0082] The slurry prepared in Examples 1-6 and Comparative Examples 1-5 was coated on copper foil, baked, cold pressed, and slit to make negative electrode sheets to test their peeling force and resistance. Lithium iron phosphate, conductive agent, solvent, and polyvinylidene fluoride were stirred evenly to make positive electrode slurry, which was evenly coated on carbon-coated aluminum foil, baked, cold pressed, and slit to make positive electrode sheets. The positive electrode sheet, negative electrode sheet, and coated separator were assembled into a lithium iron phosphate battery, and the DCR and cycle performance of the prepared lithium iron phosphate battery were tested. The test results are shown in Table 1:
[0083] Table 1
[0084]
[0085] As can be seen from Table 1, from Examples 1-2, the resistance of the electrode made of the slurry prepared by the homogenization method of the present invention can reach below 2.36 mΩ, the electrode peeling force can reach above 0.32 N, the DCR of the battery can reach below 15.5 mΩ, and the capacity retention rate after 1000 cycles at 25°C can reach above 95.8%.
[0086] By comparing Example 1 with Example 3-4, it can be seen that in the homogenization process of the present invention, the linear speed of stirring will affect the homogenization effect. When the stirring paddle rotates, the slurry with high solid content can be sheared, and the slurry can be squeezed at the same time, so that the negative electrode material and the conductive agent dispersant chain are mixed more evenly. The linear speed of stirring is associated with the properties of the negative electrode material. Since the solid content of the slurry is high in this step, if the linear speed of the stirring paddle shearing is too fast, the slurry temperature will rise. Too high a temperature will cause the long chain structure of the dispersant to break and destroy, and lose the thickening effect. At the same time, the coating on the graphite surface is uneven, resulting in unstable slurry viscosity and easy sedimentation. If the linear speed of the stirring paddle shearing is too slow, the slurry is not completely kneaded and the dispersant coating is not complete.
[0087] By comparing Example 1 with Examples 5-6, it can be seen that the amount of binder added will affect the homogenization effect. If the amount of binder added is too low, the viscosity of the slurry is too low and it cannot be well bonded to the surface of the current collector. If the amount of binder added is too large, the binder is difficult to disperse and the dispersion is uneven, and it cannot play a bonding role.
[0088] By comparing Example 1 with Comparative Examples 1-3, it can be seen that in the homogenization process, the present invention reasonably controls the order and type of adding materials in each stage, improves the stability of the slurry, and at the same time increases the solid content of the slurry, saving the coating and baking costs.
[0089] By comparing Example 1 with Comparative Examples 4-5, it can be seen that in the homogenization process of the negative electrode slurry of the present invention, the amount of dispersant added is related to the D50, tap density and specific surface area of the negative electrode material. Controlling the relationship between the dispersant and the negative electrode material can reduce the processing difficulty, improve the stability of the slurry, thereby improving the uniformity and consistency of the pole piece, and improving the performance of the battery cell. The larger the particle size of the negative electrode material, the smaller the specific surface area, so the less dispersant is required to be coated on the surface of the negative electrode material. If the dispersant is added in excess, the viscosity of the slurry will increase, which is not conducive to the coating process. On the contrary, the dispersant will not completely coat the surface of the negative electrode material, and the slurry viscosity is low, which is also not conducive to the coating process. At the same time, due to the discharge of a large amount of water during baking, it is easy to cause the pole piece to crack. The greater the tap density, the greater the slurry bulk density, the closer the contact between the particles, the more uniform the dispersant coating, and the better the slurry stability. On the contrary, the tap density is low, the negative electrode material bulk density is small, the particles are fluffy, and the dispersant is extremely difficult to coat evenly, so the slurry stability is poor, and the processing performance such as coating is poor. The larger the specific surface area, the more pores in the negative electrode material, and the more difficult it is to coat the dispersant evenly. Therefore, the kneading time, the amount of dispersant, and the shear speed must all be increased to varying degrees. The particle size, tap density, and specific surface area of the negative electrode material are interrelated. The negative electrode material has a small particle size, a large specific surface area, and a low tap density, so it is difficult to process; while the negative electrode material has a large particle size, a small specific surface area, and a high tap density, so the processing difficulty is relatively low.
[0090] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for homogenizing a negative electrode slurry, characterized in that: The homogenization method comprises the following steps: (1) mixing a negative electrode material, a conductive agent and a dispersant and stirring them in one step to obtain a mixed material; (2) mixing the mixture obtained in step (1) with the first solvent and stirring in two steps to obtain a mixed slurry; (3) mixing the mixed slurry obtained in step (2) with the second solvent and stirring in three steps to obtain a half-step slurry; (4) mixing the half-step slurry obtained in step (3) with a binder, and stirring the mixture in four steps to obtain the negative electrode slurry; Wherein, the mass ratio of the negative electrode material, the conductive agent and the dispersant in step (1) is (90-97):(0.5-0.75)a:a, a=0.17x+0.3y-0.47z, wherein x is the median particle size D50 of the negative electrode material, y is the tap density of the negative electrode material, and z is the specific surface area of the negative electrode material; The linear velocity of the two-step stirring in step (2) is (0.67-1.23) bm / s, wherein b=7.35a+0.73y.
2. The homogenization method according to claim 1, characterized in that The negative electrode material in step (1) includes any one of graphite, soft carbon, or hard carbon, or a combination of at least two of them.
3. The homogenization method according to claim 1, characterized in that The conductive agent in step (1) includes any one of conductive carbon black, graphene or carbon nanotubes, or a combination of at least two of them.
4. The homogenization method according to claim 1, characterized in that The dispersant in step (1) includes sodium carboxymethyl cellulose.
5. The homogenization method according to claim 1, characterized in that The median particle size D50 of the negative electrode material in step (1) is 5 to 20 μm.
6. The homogenization method according to claim 1, characterized in that The tap density of the negative electrode material in step (1) is 0.7 to 1.2 g / cm 3 .
7. The homogenization method according to claim 1, characterized in that The specific surface area of the negative electrode material in step (1) is 0.8 to 2.8 m 2 / g.
8. The homogenization method according to claim 1, characterized in that The stirring speed of the one-step stirring in step (1) is 1000-1800 rpm.
9. The homogenization method according to claim 1, characterized in that The stirring time in step (1) is 20 to 30 minutes.
10. The homogenization method according to claim 1, characterized in that: In step (2), the first solvent comprises water.
11. The homogenization method according to claim 1, characterized in that: The mass ratio of the mixed material to the first solvent in step (2) is 100:(30-40).
12. The homogenization method according to claim 1, characterized in that: The speed of the second step stirring in step (2) is 500-1200 rpm.
13. The homogenization method according to claim 1, characterized in that: The time of the second step stirring in step (2) is 30 to 40 minutes.
14. The homogenization method according to claim 1, characterized in that: In step (3), the second solvent comprises water.
15. The homogenization method according to claim 1, characterized in that: The mass ratio of the mixed slurry to the second solvent in step (3) is 100:(17-28).
16. The homogenization method according to claim 1, characterized in that: The stirring speed of the three steps in step (3) is 2000-2700 rpm.
17. The homogenization method according to claim 1, characterized in that: The linear velocity of the three-step stirring in step (3) is (0.89-1.56) bm / s.
18. The homogenization method according to claim 1, characterized in that: The stirring time of the three steps in step (3) is 20 to 30 minutes.
19. The homogenization method according to claim 1, characterized in that: The solid content of the half-step slurry in step (3) is 55-62%.
20. The homogenization method according to claim 1, characterized in that: The adhesive in step (4) comprises styrene-butadiene rubber.
21. The homogenization method according to claim 1, characterized in that: The mass ratio of the half-step slurry to the binder in step (4) is 100:(1-3.5).
22. The homogenization method according to claim 1, characterized in that: The stirring speed of the four steps in step (4) is 500-1200 rpm.
23. The homogenization method according to claim 1, characterized in that The linear velocity of the four-step stirring in step (4) is (a×z+3.2y) m / s.
24. The homogenization method according to claim 1, characterized in that The stirring time of the four steps in step (4) is 30 to 40 minutes.
